Induction of z-conformation in ribosomal RNA by Z-DNA binding domain Zα of the human double-stranded RNA deaminase I (ADAR1) - Zhao, Jing (2012)
The Z-DNA/Z-RNA binding domain Zα of the human RNA editing enzyme double-stranded RNA deaminase I (ADAR1) is found to influence various biological functions, such as the DNA-mediated innate immune response, and transcriptional modulation of gene expression. Recently our collaborators have discovered that ZαADAR1 binds stably to ribosomes inside E. coli and human cells leading to translational inhibition in vitro and in vivo (Feng, Li et al. 2011). We contributed to this fundamental discovery by demonstrating an involvement of the Z-RNA conformation in this process (Feng, Li et al. 2011). As a means to characterize the induction of Z-RNA we employed solution NMR spectroscopy. We determined 3D solution structures of ZαADAR1 and ZαADAR1 mutant (N43A, Y47A) and compared binding modes of these two proteins to Z-DNA, short (5-32 residues) dsRNA oligonucleotides derived from rRNA and E.coli ribosomes. We found that ZαADAR1 has the ability to interact with Z-DNA, short dsRNA from rRNA and E.coli ribosomes with sufficiently high affinity and induce the B- to Z- or A- to Z- conformational changes in DNA and RNA, respectively. ZαADAR1 mut also has the ability to interact with DNA and RNA, but with significantly lower affinity comparing to its wild type. ZαADAR1 mut also lacks the ability to induce Z-conformation in DNA and RNA. We also mapped the binding interfaces of ZαADAR1 to Z-DNA, Z-RNA and E.coli ribosomes, and found them to be identical. Based on this finding, we proposed that the role of ZαADAR1 in binding to ribosomes and inhibiting translation is to recognize potentially Z-forming structures and/or induce localized structural transitions from A- to Z-conformations in ribosomal RNA. In order to provide theoretical foundations for the analysis of NMR spectral responses of ZαADAR1 to ribosomes we attempted to extend the conventional NMR relaxation theory to include a semi solid-state treatment of nuclear spin dynamics in large complexes. The main challenge to the classical NMR theory arises when one of the binding partners is so large that in the chemical shift time scale of solution NMR (milliseconds) it can be considered as practically static or solid-state-like. Therefore, our theoretical model shall predict whether the chemical shifts perturbations observed through the small binding partner can be used to delineate the involved binding interface, and whether changes of the positions of NMR resonances or only attenuation of the cross-peak intensities are to be expected upon binding to a solid partner.